Coaching clinic contract relax and hold relax exercise optimising range of motion in sports injuries - Sutoro; Daniel Womsiwor; Saharuddin Ita; Ipa Sari Kardi; Vinsensia Awutet Amjaram; Pian Asso; Hans Januaris Orboi (University of Merdeka Malang, 2025)
This community service programme aims to implement Contract Relax and Hold Relax technique training clinics to optimise Range of Motion (ROM) in Papuan athletes who have suffered sports injuries. It uses an Assets-Based Community Development (ABCD) approach through presentations and training clinics. The study involved Papuan athletes as participants, with a majority of males (62.5 percent) and a dominant age group of 15-16 years (47.9 percent). According to the injury history, 41.7 percent of participants reported experiencing injuries 2-3 times in the past year. The results showed a significant increase in athletes' understanding of rehabilitation techniques. The highest growth occurred in the knowledge of the Contract Relax principle (87.44 percent) and its application to injuries (85.68 percent). In practical skills, the greatest improvement was in mastery of the Contract phase (95.7 percent), followed by the Hold technique (95.0 percent). The implementation of techniques in injury cases showed optimal results for lower back pain with a 56.0 percent increase in ROM, followed by ankle sprains (45.1 percent). Participant satisfaction evaluations showed the highest ratings for instructor competence (4.89/5) and quality of practical application (4.70/5). This program has proven effective in enhancing the knowledge, skills, and ROM of Papuan athletes with sports injuries through the Contract Relax and Hold Relax coaching clinic.